Analisis Kemampuan Literasi Matematis Siswa Melalui Komik Matematika Berbasis Pembelajaran Berbasis Masalah - Novferma, Novferma; Romundza, Febbry; Yenzi, Indah Pristy (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Indonesian students' ability in mathematical literacy is classified as low; this is shown in several PISA survey results. What causes students' low mathematical literacy abilities in Indonesia is the need for more application of learning models and media that support students' mathematical literacy abilities. This research analyzes students' mathematical literacy skills using problem-based learning-based mathematical comics. This research is a type of qualitative research. The subjects of this research involved 25 class VIII—1 students at one of the schools in Batanghari, namely SMPN 21 Batanghari. The data collection technique in the study was a mathematical literacy ability test consisting of 5 essay questions. Data analysis in this research includes data reduction, data presentation, and concluding/verification. The research results showed that of the 25 students who took the mathematical literacy ability test, as many as 11 students, or 44%, had high levels of mathematical literacy skills. As many as 14 students, or 56% of students, had moderate mathematical literacy skills. No students had average levels of mathematical literacy skills. Low-level mathematics. Thus, it is concluded that students' mathematical literacy abilities after learning using problem-based learning-based mathematical comics fall into the category of medium-level mathematical literacy abilities as seen from the average score obtained on the students' mathematical literacy ability test, which is 79,72.